Potential For Ecotourism Development Of Mount Ranaka At Ruteng Nature Tourism Park - Ina Maryam Jamilah; Maria M. E. Purnama; Yusratul Aini; Nixon Rammang (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
This study aims to identify the potential of natural resources on Mount Ranaka (Mt Ranaka) that can be used as ecotourism objects and measure the motivation, perception and preferences of visitors towards ecotourism in the Mt Ranaka area. The research methods used include field observations, interviews and questionnaires, and literature studies, with data analysis using descriptive qualitative analysis, likert scale, and Natural Tourism Attraction Object (ODTWA) analysis. The results of the study show that Mt Ranaka has ecotourism potential in the form of lakes, flora and fauna potential, religious potential and natural attractions that are high and are classified as suitable for development as an ecotourism destination based on the results of the ODTWA feasibility index assessment. Visitor motivation is dominated by the desire to enjoy nature and adventure activities, visitor perception is in the good category, and visitor preferences show trekking activities as the main choice. Keywords: Development, Ecotourism, Ruteng Nature Tourism Park